Pembelajaran sosial dalam pengelolaan hutan komunitas: social learning in community forests - Wollenberg, Eva Karoline; Edmunds, D.; Buck, L.; Fox, J.; Brodt, S. (Pustaka LATIN and CIFOR, 2005)
How can different interest groups engage together in learning processes that enable them to better manage community forests? In this volume, practitioners from eight countries document their experience with the aim of identifying how to characterize social learning, as well as how to improve upon current practice. Analysis of current approaches to facilitation and the circumstances or platforms of learning indicate the need for more attention to the different avenues and styles of learning and the potential benefits of using multiple avenues. Learning styles and approaches need to be responsive to stakeholders’ preferences, culture, and changes in management needs. Multiple approaches are likely if the goal is to reach all the necessary parties and to be relevant to changing conditions over time. In documenting these experiences, the authors link their observations to concepts, labels and the theory of social learning to further advance our general understanding of multi-stakeholder processes in forest management.